A new type of Sr(Zr0.2Hf0.2Ce0.2Yb0.2Me0.2)O3−x (Me = Y, Gd) high‐entropy ceramics used in thermal barrier coatings. Issue 3 (23rd November 2022) - Zhan, Hao; Ma, Wen; Han, Xinxin; Liang, Weicheng; Hao, Jiajing; Dong, Hongying; Bai, Yu; Liu, Hongxia; Meng, Xiangfeng
Abstract: Seeking for new ceramics with excellent thermophysical properties as thermal barrier coatings candidate materials has become a hot research field. In this study, Sr(Zr0.2 Hf0.2 Ce0.2 Yb0.2 Me0.2 )O3− x high‐entropy ceramic powders were successfully synthesized by the method of solid‐state reaction, and the ceramics with single phase were prepared by pressureless sintering at 1600°C. The phase composition, microstructure, element distribution, high‐temperature thermal stability, and thermophysical properties of the ceramics were studied. The results showed that Sr(Zr0.2 Hf0.2 Ce0.2 Yb0.2 Me0.2 )O3− x ceramics were composed of SrZrO3 phase and the second phase of AB2 O4 spinel (i.e., SrY2 O4 and SrGd2 O4 ). The content of the second phase was gradually increased after heat treatment at 1400°C, which significantly improved the thermophysical and mechanical properties of the ceramics. The microhardness and fracture toughness of the ceramics were improved compared with that of SrZrO3 . The thermal conductivities of Sr(Zr0.2 Hf0.2 Ce0.2 Yb0.2 Me0.2 )O3− x (Me = Y, Gd) ceramics were 1.30 and 1.28 W m −1 K −1 at 1000°C, which were about 35% and 40% lower than that of SrZrO3 (1.96 W m −1 K −1 ) and yttria‐stabilized zirconia (2.12 W m −1 K −1 ), respectively. The thermal expansion coefficients of Sr(Zr0.2 Hf0.2 Ce0.2 Yb0.2 Me0.2 )O3− x (Me = Y, Gd) ceramics were 12.8 × 10 −6 and 14.1 × 10 −6 K −1 at 1300°C, respectively, which was more closer to the superalloys compared with SrZrO3 ceramic (11.0 × 10 −6 K −1 ).